CCURRENT TRENDS IN INFANT MORTALITY AND PERINATAL LOSS RATES IN ST. PETERSBURG - N. V. Andriyanycheva; A. S. Simakhodsky (Вопросы современной педиатрии, 2013)
Over the last decade, the positive trends in the demographic indicators of St. Petersburg are related, among the others, to the sustainable reduction of infant mortality, however the specifics of demography of a large city of federal importance is characterized by high migratory increase. Now the megalopolis is the region with the lowest infant mortality rates. This target demographic indicator is the pride of St. Petersburg and is closely monitored. Achievements in reducing of infant mortality were fulfilled through a system of work with pregnant women and newborns with low, very low and extremely low birth weight. Significant impact has also been adopted by the legislative acts, which, at present, are included into a single normative document — «Social code of St. Petersburg». The main purpose of the article is an extended analysis of the mortality rate due to transition to the new medical criteria of birth. The analysis demonstrates that the transition to the new criteria of live birth has made changes in the structure of infant and perinatal mortality, which requires further improvement and new approaches to the executive monitoring of this important social marker.